Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. The degree of suitability of the organizational climate in Yemeni private universities  from the point of view of academic and administrative leaders in these universitiesMRS. Ashwaq Yahya Yahya Al-Aush, Prof.Dr. Fahd Saleh Qasem Maghrabah2. The effectiveness of a program based on the constructivist approach to teaching jurisprudence  in developing health concepts for first-year secondary students in Amran Governorate in the Republic of YemenThe researcher / Adnan Ibrahim Mohammed Hamdan3. Use of modern techniques and ways to activate them to improve the performance of general education schools in the State of Palestine in the light of recent trendsMr. Fadi Ahmad Shaheen
Keywords: Journal of Educational and Psychological Sciences